Creep-rupture behavior of AISI 347 austenitic stainless steel foils at different temperature and stress levels [electronic resource] - 187021 Hassan Osman Ali; Mohd. Nasir Tamin, supervisor; Fakulti Kejuruteraan Mekanikal (2011)
Thesis (Ph.D (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2011